ANTENA ARRAY LINIER VERTIKAL UNTUK MENINGKATKAN DAYA TERIMA SINYAL TELEVISI DIGITAL PADA WILAYAH PEDESAAN (RURAL AREA) - Sandri Priatmo; Yulindon Yulindon; Firdaus Nursal (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The transition from analog to digital television broadcasting in Indonesia improves picture and sound quality; however, signal reception in rural areas remains a challenge due to long distances from transmitters and unfavorable topography. Conventional antennas and signal boosters have not provided optimal performance. This study aims to design a vertical linear antenna array with a stacking configuration to enhance digital television signal reception in the Ultra High Frequency (UHF) band. The antenna design was carried out through theoretical calculations, simulation, and optimization using CST Studio Suite 2019. The analyzed parameters include return loss, VSWR, gain, bandwidth, and radiation pattern. Simulation and testing results show that the antenna achieves a return loss below −10 dB, VSWR less than 2, gain above 10 dBi, and a unidirectional radiation pattern. The proposed antenna effectively improves digital television reception quality in rural areas.